Exploring optimal HAART adherence rates in Ethiopian adults: a systematic review and meta-analysis - Mengistie Yirsaw Gobezie; Nuhamin Alemayehu Tesfaye; Tewodros Solomon; Mulat Belete Demessie; Teklehaimanot Fentie Wendie; Getachew Tadesse; Tesfaye Dessale Kassa; Fentaw Tadese Berhe; Fentaw Tadese Berhe; Minimize Hassen (Frontiers Media S.A., 2024)
BackgroundOptimal medication adherence is vital for the successful implementation of highly active antiretroviral therapy (HAART) in managing HIV infection. Global efforts aim to minimize the burden of antimicrobial resistance (AMR), including HIV-associated drug resistance.MethodsThis systematic review and meta-analysis followed PRISMA guidelines and searched multiple databases for eligible studies published until July 10, 2023. Eligible studies focused on Ethiopians receiving HAART, reported the prevalence of optimal adherence, and used appropriate assessment tools. Quality of included studies was assessed using JBI checklists A weighted inverse variance random-effects model was applied to calculate the pooled prevalence.ResultsOur meta-analysis aimed to determine the pooled prevalence of optimum Highly Active Antiretroviral Therapy (HAART) adherence among HIV-positive adults in Ethiopia and explore variations based on assessment methods, recall periods, and regional factors. The estimated national pooled prevalence of optimal HAART adherence was 79% (95% CI: 74-83, I2 = 98.1%; p-value < 0.001). Assessment methods revealed a prevalence of 64% (95% CI: 54-73) using structured assessment and 82% (95% CI: 78-86) with self-reporting. Optimum adherence varied based on recall periods, ranging from 78 to 85% with self-reporting. Heterogeneity analysis indicated substantial variation (I2 = 98.1%; p-value < 0.001), addressed through subgroup analysis, sensitivity analysis, and univariate meta-regression. Subgroup analysis based on region identified varying prevalence: SNNPR (83%), Oromia (81%), Amhara (79%), and Addis Ababa (74%). Considering the 2018 guideline revision, year-based subgroup analysis showed a prevalence of 78% and 78% before and after 2018, respectively. Sensitivity analysis demonstrated the stability of results, with excluded studies having a minimal impact. Publication bias analysis indicated an absence of bias, as evidenced by a non-significant Egger's regression test (p-value = 0.002) and no adjustment in trim and fill analysis.ConclusionsThe estimated overall prevalence of optimal adherence was 79%, indicating a substantial level of adherence to HAART in the Ethiopian context. The study identified variations in adherence levels based on assessment methods and recall periods, highlighting the importance of considering these factors in evaluating adherence rates. These insights contribute valuable information for policymakers, healthcare practitioners, and researchers working toward enhancing HAART adherence in Ethiopia.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=459679